2015
DOI: 10.1038/ncomms8857
|View full text |Cite
|
Sign up to set email alerts
|

Developmental disruptions underlying brain abnormalities in ciliopathies

Abstract: Primary cilia are essential conveyors of signals underlying major cell functions. Cerebral cortical progenitors and neurons have a primary cilium. The significance of cilia function for brain development and function is evident in the plethora of developmental brain disorders associated with human ciliopathies. Nevertheless, the role of primary cilia function in corticogenesis remains largely unknown. Here we delineate the functions of primary cilia in the construction of cerebral cortex and their relevance to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
123
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(127 citation statements)
references
References 69 publications
(108 reference statements)
4
123
0
Order By: Relevance
“…Therefore, precise regulation of OPC proliferation dynamics is key to generating appropriate number of functional oligodendrocytes and maintaining normal myelination [47]. While BubR1 is known as a critical cell cycle regulator in the context of early cortical neural development [48] and tumorigenesis [10], its function in OPC proliferation and their development was not known. Intriguingly, previous studies have identified several components that directly interact with BubR1 in regulating oligodendrocyte development and myelination.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, precise regulation of OPC proliferation dynamics is key to generating appropriate number of functional oligodendrocytes and maintaining normal myelination [47]. While BubR1 is known as a critical cell cycle regulator in the context of early cortical neural development [48] and tumorigenesis [10], its function in OPC proliferation and their development was not known. Intriguingly, previous studies have identified several components that directly interact with BubR1 in regulating oligodendrocyte development and myelination.…”
Section: Discussionmentioning
confidence: 99%
“…The critical role of primary cilia in brain development and function is evident in human ciliopathies (Guemez-Gamboa et al, 2014; Guo et al, 2015), where disrupted cilia function lead to brain malformations and behavioral deficits. Many candidate genes for neurodevelopmental disorders such as ASD, schizophrenia, and intellectual disabilities affect cilia function (Hildebrandt et al, 2011; Lee and Gleeson, 2011; Louvi and Grove, 2011; Marley and Von Zastrow, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To assess the specific requirement of interneuronal primary cilia signaling in the construction of inhibitory circuit, we conditionally disrupted primary cilia function in the striatal INs originating from the medial ganglionic eminence (MGE). Arl13b, a small GTPase of the Arf/Arl family, is specifically localized to cilia and is required for cilium’s ability to function as a signaling hub (Cantagrel et al, 2008b; Caspary et al, 2007; Guo et al, 2015; Higginbotham et al, 2012b; Higginbotham et al, 2013). Deletion of Arl13b impairs primary ciliary signal transduction, without physically ablating ciliary structure, and thus provides a unique model for examining the specific role of primary cilia signaling in interneuronal morphology, connectivity, and synaptic integration.…”
Section: Introductionmentioning
confidence: 99%
“…46 A recent study in which 30 of the genes known to cause neural development-associated ciliopathies were knocked down by shRNA in mice, reveals that actually many of them are necessary for most of the neurogenic processes described above. 47 One open question is if these genes (as many others) actually cause neurodevelopmental defects through the cilium or through extraciliary functions they may have, a possibility that will undoubtedly increase the level of complexity associated to the role of the cilium and ciliary proteins in these processes. In summary, a complete and in-depth study of the dynamics of these organelles, the identification of the relevant signaling cascades operating through them, and a systems biology approach to understand the crosstalk between signaling pathways will be required to completely understand the role of cilia in neurogenesis and neuronal differentiation.…”
Section: Discussionmentioning
confidence: 99%